Bio-Fabrication: Convergence of 3D Bioprinting and Nano-Biomaterials in Tissue Engineering and Regenerative Medicine - Di Marzio, Nicola; Eglin, David; Serra, Tiziano; Moroni, Lorenzo (Frontiers in Bioengineering and Biotechnology, 2020)
3D Bioprinting (3DBP) technologies open many possibilities for the generation of highly complex cellularized constructs. Nanobiomaterials have been largely used in tissue engineering and regenerative medicine (TERM) for different purposes and functions depending on their intrinsic properties and how they have been presented in the biologic environment. Combination of bioprinting and nanobiomaterials paves the way for unexpected opportunities in the biofabrication scenario, by improving critical weakness of these manufacturing processes while enhancing their efficiency by spatially arranging nanofeatures. 3D organization of cells is fundamental for a successful design and maturation of native tissues. A critical challenge for the production of biological constructs is to support and guide cell growth toward their natural microenvironment, ensuring a harmonious presence of specific biochemical and biophysical cues to direct cell behavior. Also, precise arrays of stimuli need to be designed to induce stem cell differentiation toward specific tissues. Introducing nano-sized bioactive material can direct cell fate, playing a role in the differentiation process and leading to the biofabrication of functional structures. Nanocomposite bio-ink can be used to generate cell instructive scaffolds or either directly printed with cells. In addition, the presence of nanoparticles within 3D printed constructs can lead to control them through multiple external physical stimuli, representing an additional tool for healthcare applications. Finally, there is an emerging interest to create biological constructs having active properties, such as sensing, motion or shape modification. In this review, we highlight how introducing nanobiomaterials in bioprinting approaches leads to promising strategies for tissue regeneration.